Globalisation and poverty changes in Colombia - Maurizio Bussolo; Jann Lay (OECD, 2003)
Assessing the final impact of globalisation on poverty is a difficult task: i) globalisation affects poverty through numerous channels; ii) some linkages are positive and some are negative and therefore cannot be analysed qualitatively but require quantitative assessments, i.e. formal numerical models; and iii) trade expansion and growth (key aspects of globalisation) are essentially macro phenomena, whereas poverty is fundamentally a micro phenomenon. In this paper we use a new method that combines a micro-simulation model and a standard CGE model. These two models are used in a sequential fashion (as in a recent paper by Robilliard et al., 2002). The CGE model and the micro-simulation model are calibrated using a recent SAM and household survey for Colombia and together they capture the structural features of the economy and its detailed income generation mechanisms. We use this framework to analyse the important income distribution and poverty changes occurred with the great trade liberalisation of the 1990s. A major policy conclusion is that trade liberalisation can substantially contribute to improve the poverty situation. Abstracting from simultaneous additional shocks and labour supply growth, the beginning of the 1990s tariff abatement seems to have accounted for a very large share of the total reduction in poverty recorded from 1988 to 1995. This holds in particular for rural areas. Furthermore distributional impacts differ fundamentally between rural and urban areas, and our methodology highlights that aggregate net results, such as the change in the poverty ratio (headcount), conceal important flows in and out of poverty. This framework allows us to capture important channels through which macro shocks affect household incomes and possibly to help in designing corrective pro-poor policies.
Keywords: 330; Armutspolitik; Entwicklungspolitik; Entwicklung; Globalisierung; Kolumbien